DAMPAK APLIKASI PERILAKU CARING DALAM PENDIDIKAN TAHAP PROFESI NERS: STUDI FENOMENOLOGI - Afina Muharani Syaftriani; Muchti Yuda Pratama (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Caring behavior is an act based on caring, affection, skill, empathy, responsibility, sensitivity and support. Provision of nursing services based on caring behavior can improve the quality of health services. Caring behavior is not only performed by nurses but also performed by students who are running the professional education phase ners in the hospital. The application of caring behavior to students in professional education is very important because it is the first place for students to learn about the values and essence of their profession. This study aims to explore the impact of caring behavioral application in professional education stage ners. This research uses phenomenology design. The sampling technique used was purposive sampling with a total of ten participants. The data was collected at Nursing Faculty of University of Sumatera Utara from February to April 2015. Data analysis in this research used Collaizi method. This study found 5 themes of caring behavioral application impact in professional education ners stage, that is 1) professional students ners experiencing inner satisfaction, 2) professional students ners feel happy, 3) patients feel comfortable, 4) accelerate the healing process of patients, and 5) knowledge patient increases. Given the magnitude of the impact of caring behavior, it is recommended to students of professional education stage ners to continue to improve caring behavior to patients. Furthermore, for nursing education institutions or hospitals can create caring behavior standards so as to improve the quality of service to patients.Keywords: impact of caring behavior, professional education stage ners, phenomenology study